Charlee Chaplin : Aap Beeti - Chaplin, Charlie, 1889-1977; Translated by Qaisar Chohan (Lahore, Pakistan Ilam-o-Irfan Publishers, 2008)
Chaplan recalls "his boyhood; the early, casual days of the movies; how he evolved his style, his costumes, his plots, his sudden dazzling success; how he chose his leading ladies; his encounters with great stars and world figures, from Mary Pickford to Gandhi to Bernard Shaw to FDR; his emotional involvements and his four marriages . . . and the political accusations that made him decide to leave the United States."
Include Illustration and List of Flims
Keywords: Motion picture actors and actresses